The antecedents of women's external locus of control: Associations with characteristics of their parents and their early childhood. Issue 1 (January 2017) - Golding, Jean; Gregory, Steven; Iles-Caven, Yasmin; Nowicki, Stephen
Abstract: Locus of control (LOC) measures individuals' expectancies regarding their ability to affect what happens to them based on how they behave. The more they believe their behaviour has something to do with what happens to them the more internal they are. In contrast the more they perceive that what happens to them is beyond their control and determined by luck, fate, chance or powerful others the more external they are. Copious research findings suggest that external LOC (ELOC) is associated with many adverse personal, social, academic and health outcomes. In spite of its importance in so many areas of human behaviour relatively little is known about the features of the early background of individuals that contributes to these expectancies. This is the first in a number of studies that will suggest possible antecedents and consequences of having a high ELOC. The study takes advantage of the data collected in the Avon Longitudinal Study of Parents and Children (ALSPAC), which started by studying pregnancies in 1991–1992 of residents in an area of south-west England. Over 12000 of the women who enrolled during pregnancy completed a set of questions in mid-pregnancy from which an LOC score was computed. ELOC was defined as a score greater than the median. The relationships with characteristics of the women's parents and her early childhood (<6 years) are considered first as unadjusted odds ratios and then as adjusted after analysis using hierarchical sets of stepwise logistic regressions. The relative contributions to the women's ELOC was measured using a goodness-of-fit (GOF) measure. The analyses demonstrated the independent importance of maternal and paternal backgrounds as well as features of her early childhood (<6 years). The final model identified nine independent features (each with P < 0.0001): year of birth of her mother, maternal and paternal education levels, father smoked, mother smoked when pregnant, year of birth of study woman, the number of older siblings she had, whether her father was absent during this period, and whether she spent her childhood in the study area. In conclusion, the woman's LOC appears to be independently influenced by a number of characteristics which may give clues as to possible mechanisms—and how internality may be supported in the future. Subsequent papers will assess both whether features of later childhood influence the woman's LOC and whether the LOC of men in the study have similar antecedents.